Resilience elements to combat counterfeit medicines in supply chain - Lima, Flávia Renata Pinho de (Universidade Federal de São Carlos, 2018)
Supply chains are becoming more complex and vulnerable to specific disturbances scenarios, critical to business continuity. Counterfeiting is one of them, especially in markets where counterfeit products affect directly consumers’ health, such as food, beverage and medicines. However, few authors have investigated how to analyze this disturbance from a managerial perspective. This study claims that supply chain resilience is a dynamic solution applicable to combat a disturbance in constant growth and innovation: counterfeiting. To bridge this gap, namely the lack of understanding in how to increase resilience to counterfeits, the purpose of this study is to understand how resilience elements influence the combat of counterfeit medicines. To do so, we developed systematic literature review, using the QDA Miner software to support the content analysis. After a careful screening, we selected 84 articles between 2002 and Oct/2016. The systematic review reveals 13 resilience elements and 16 counterfeit anti- measures. Furthermore, reengineering, collaboration, visibility, innovation, SCR culture and trust appeared as six key-elements to combat counterfeit. After a literature review, we conducted an empirical research – case study, to pursue our exploratory purpose. The case study encompasses two medicines supply chains, with two pharmaceuticals (focal companies) and members downstream, and agencies and associations that work across the medicines supply chain to combat counterfeits. The empirical analysis enabled a deeper investigation of the resilience elements and counterfeit anti-measures applied. Our findings show that, in accordance with literature, collaboration, trust and visibility, are crucial elements to strengthen resilience against counterfeiters. Furthermore, different from literature review, information sharing and sensing appeared as elements highly associated in counterfeit combat, leveraged by the existence of a huge amount of data and the possibility of improving the decision-making process. Thus, this study contributes to the field by (i) proposing a framework for increasing resilience to counterfeit in medicines supply chain, which characterizes the dynamics among resilience elements and counterfeit anti-measures and discusses the role of collaboration and information sharing such as barriers to increase resilience. (ii) By suggesting new avenues of research, such as exploring tradeoffs between resilience and anti-counterfeit literature, investigating the effectiveness of implementing each resilience element in counterfeit combat, and analyzing different sectors highly targeted by counterfeiters, such as fashion and food.
Elementos de resiliência para combater a contrafação de medicamentos na cadeia de suprimentos
Keywords: Cadeia de suprimentos; Elementos de resiliência; Medidas anti-contrafação; Cadeia de medicamentos; Supply chain; Resilience elements; Counterfeit anti-measures; Medicines supply chain; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO